Analisis Pemotongan Imbalan Nazhir Pengelolaan dan Pengembangan Harta Benda di Wakaf Salman ITB - Alpiah Trisna Dewi; Ifa Hanifia Senjiati; Zia Firdaus Nuzula (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. The review of the Indonesian Waqf Board (PBWI) Regulations and the Statement of Islamic Financial Accounting Standards (PSAK) form the basis for analyzing the practice of cutting a 10% fee at the start of a contract. This study uses a qualitative method with the research object of Wakaf Salman Bandung which applies deductions to nazhir fees. The results of the research are (1) PBWI allows Nazhir to receive operational or administrative costs, allows him to receive compensation from the management and development of waqf up to a maximum of 10% of the net proceeds from the management and development of waqf assets. (2) PSAK explains that nazir has the right to receive a maximum compensation of 10% of the net proceeds. (3) the implementation of the 10% deduction at the beginning of the waqf contract in the Salman Waqf is recognized as an administration fee and does not yet have the results of waqf management. (4) PBWI and PSAK analysis in Wakaf Salman ITB is permissible if it is for operational funds and there is no recognition of the results of management and development of waqf assets. Abstrak. Tinjauan Peraturan Badan Wakaf Indonesia (PBWI) dan Pernyataan Standar Akuntansi Keuangan Syariah (PSAK) menjadi landasan dalam menganalisis praktik pemotongan biaya 10% di awal akad. Penelitian ini menggunakan metode kualitatif dengan objek penelitian Wakaf Salman Bandung yang menerapkan pemotongan imbalan nazhir. Hasil penelitian adalah (1) PBWI memperbolehkan nazhir menerima biaya operasional atau administrasi, memperbolehkan menerima imbalan hasil pengelolaan dan pengembangan wakaf maksimal 10% dari hasil neto pengelolaan dan pengembangan harta wakaf. (2) PSAK menjelaskan bahwa nazhir berhak untuk mendapatkan imbalan maksimal 10% dari hasil neto. (3) implementasi pemotongan 10% di awal akad berwakaf pada Wakaf Salman diakui sebagai biaya administrasi dan belum memiliki hasil pengelolaan wakaf. (4) analisis PBWI dan PSAK di Wakaf Salman ITB adalah diperbolehkan jika untuk dana operasional serta belum ada pengakuan hasil pengelolaan dan pengembangan aset wakaf.